Jesus "at home": did Jesus have a house in Capernaum? - Doole, J. Andrew (Protokolle zur Bibel, 2017)
There is an observable tension among sayings and traditions in the canonical gospels that paint a positive image of family life and those which appeal to the breakdown of traditional family ties. The same tension may be seen between passages which describe a homeless Jesus and those which speak of Jesus “at home”. The site of apparently early Christian significance in Capernaum is needlessly associated with Peter (and Andrew), on the assumption that “the house” in the village where Jesus is to be found must be that of his first disciples. There is however much evidence in the gospels which would lead one to conclude that the earliest days of the Jesus-movement were based for the most part in Jesus’ house in Capernaum.